Methodology for assessing the effectiveness of the tax base among redistribution the largest taxpayers - K. A. Zaharova; N. E. Aktaev; N. V. Ivanova (Модернизация, инновация, развитие, 2023)
Purpose: the article is aimed at presenting the author’s methodology for evaluating the efficiency of redistribution of the tax base within the consolidated group of taxpayers (hereinafter REAG) the construction of which is based on the determination of relationships and assessment of the degree for influence of tax deductions on the operating profit of the enterprise.Methods: in the part of the study of the tax base and REAG contributions, methods of applying statistical analysis were used, including the study of the structure and dynamics of tax payments of the enterprise. As part of the construction of the model, this article provides the correlation and regression analysis, providing for several stages related to the application of the specific tax regime of REAG as the significant factor of influence on the process of distribution of the taxable base of the organization. The data of public joint-stock company «Oil company «ROSNEFT» were used to assess the influence on the operating profit of the enterprise of the taxes paid. The graphical analysis was used to visualize the data.Results: in the course of the study, the degree of influence of the volume for sales of products, selling prices, decrease of the cost and changes in the sales structure on the volume of tax payments of the enterprise was assessed. These factors determine the effectiveness of the REAG’s tax regime, as they represent the company’s profit and therefore affect the amount of income tax. This dependence is reflected in the developed econometric model, which determines the share of each factor in the total income tax of the enterprise, which allows to optimize the tax base of the organization in the future.Conclusions and Relevance: the analysis revealed the need to improve the efficiency of income tax payment. In response, the methodology for improving the tax regime is proposed. Tax optimization measures include two directions: the process of redistribution of the tax base and the extension of the term for performance of tax obligations within the combined group (from earlier to later). These measures will reduce the risks of taxpayers.